2020
DOI: 10.1002/anie.202003064
|View full text |Cite
|
Sign up to set email alerts
|

Precision Molecular Threading/Dethreading

Abstract: The general principles guiding the design of molecular machines based on interlocked structures are well known. Nonetheless, the identification of suitable molecular components for a precise tuning of the energetic parameters that determine the mechanical link is still challenging. Indeed, what are the reasons of the “all‐or‐nothing” effect, which turns a molecular “speed‐bump” into a stopper in pseudorotaxane‐based architectures? Here we investigate the threading and dethreading processes for a representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 132 publications
4
28
0
Order By: Relevance
“…Upon addition of G1, characteristic proton shifts are observed in the 1 H NMR spectra of stable-cis-3 ([D 6 ]acetone solution, Figure 3 b). [26] Proton H f of stable-cis-3 shifted upfield with Dd of À0.119 ppm (Supporting Information, Figure S14). Protons H Ar and H 1' exhibited strong coupling with protons H crown ether , as evident from the two-dimensional nuclear Overhauser effects spectroscopy (NOESY; Supporting Information, Figure S15a).…”
Section: Resultsmentioning
confidence: 99%
“…Upon addition of G1, characteristic proton shifts are observed in the 1 H NMR spectra of stable-cis-3 ([D 6 ]acetone solution, Figure 3 b). [26] Proton H f of stable-cis-3 shifted upfield with Dd of À0.119 ppm (Supporting Information, Figure S14). Protons H Ar and H 1' exhibited strong coupling with protons H crown ether , as evident from the two-dimensional nuclear Overhauser effects spectroscopy (NOESY; Supporting Information, Figure S15a).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been recently reported that the possibility of undergoing threading/dethreading movements in related DB24C8-based pseudorotaxanes is determined by the ability of the macrocycle to adapt the size and shape of its cavity via room-temperature vibrations in order to accommodate a bulky molecular fragment. 61 The dynamic behavior of rotaxane 1 2+ can be qualitatively summarized with the aid of a simplified three-dimensional potential energy surface (PES) diagram (Figure 5A) taking the CN-CO torsional angle of the amide group and the distance between the centroids of the ring and axle components as the reaction coordinates. The graph shows that the two experimentally observed isomerization paths in 1 2+ can be associated with two different reaction mechanisms that occur along orthogonal reaction coordinates, namely, CN-CO bond rotation (orange trajectories) and ring shuttling (magenta trajectories).…”
Section: Ll Open Accessmentioning
confidence: 99%
“…However, previous studies on rotaxanes indicated that although the inclusion of solvent molecules decreases the barriers by about 15 kcal mol –1 , the transition state structures do not change appreciably with respect to vacuum calculations. 53 Therefore, although we acknowledge that all barriers are quantitatively overestimated, we are confident that the free energy path provides a qualitatively correct picture of the shuttling process. The profile displays three free energy wells with comparable depth characterized by a very different mutual arrangement of the molecular components.…”
Section: Resultsmentioning
confidence: 77%
“…The rotation of Tz during the transit is accompanied by low-energy synchronous vibrations of the crown ether ring, which provide the appropriate deformation needed to accomplish the shuttling. 53 In particular, Movie S1 highlights that a rotation of nearly 90° of the Tz moiety occurs along the B → A path, whereas no similar rotation of the Tz group has been detected during the B → C transit ( Movie S3 ). Finally, Movie S2 illustrates the proximity of the rings to share the complexation of the triazolium station.…”
Section: Resultsmentioning
confidence: 99%